Single mothering as experienced by Burundian refugees in Australia: a qualitative inquiry - Lily P. Tsai; Jennieffer A. Barr; Anthony Welch (BMC, 2017)
Abstract Background Refugee mothers have fled from their homeland to escape persecutions with their children only to find other threats to their well-being in the new country. Building on previous research, it is known that being a new immigrant is challenging and requires adaptation. The adaptation process, known as acculturation, may not be successful leading to psychological distress. It is also known that a generation gap can occur when children acculturate faster than their parents. What was lacking was understanding about the experiences of single refugee mothers. Methods Interpretative phenomenological study was undertaken to explore the lived experiences of eight Burundian refugee single mothers in Australia. Data were collected by in-depth interviews. Each interviews were transcribed and analyzed using thematic analysis. Results Findings revealed three themes. First theme 'Traditional mothering practices of Burundian culture' illustrated mothering strategies as practiced prior to their arrival in Australia including mothering with sufficient social support, strong position of parents, and regular use of physical disciplining. Second theme 'Challenges identified after arrival to new country' revealed that mothers felt their children acculturated faster than themselves which led to intergenerational gap. This has also led participants to live in a continuous dilemma, experiencing inner conflicts and struggles associated with their mothering practices, especially when mothers had arrived with a lack of knowledge relating to acceptable mothering practices in a new culture. Final theme, 'Reforming family life in Australia' highlighted the decisions made by single refugee mothers which is to embrace both new and original cultures, leading to successful acculturation. However, lack of appropriate knowledge of acceptable mothering practices led to involvement of legal authorities who threatening to remove children from the mother's care. This has led mothers feeling change of power from 'mother to child, 'to child to mother', raises concerns for family wellbeing. Conclusions A need for parenting information when entering a new country including education about any legal obligations for parents such as a Child Protection Act will assist successful acculturation. As nurses are likely to encounter refugee single mothers, they are well placed to provide support and education to new refugee single mothers.